(untitled) (Current Horticulture, 2024)
Forty peach (Prunus persica L.) genotypes were studied for physico-chemical and yield attributes grown under temperate environment using Mahalanobis D2 statistics at ICAR-Central Institute of Temperate Horticulture, Srinagar (Jammu & Kashmir) during 2016-2018. Most of the genotypes differed significantly for fruit colour, physico-chemical and yield attributes when subjected to multivariate analysis. The maximum standard deviation was observed for fruit weight, followed by firmness index, fruit width and least for fruit shape index and titratable acidity. The cluster analysis classified genotypes into two major groups. The first group possessed superior attributes in terms of highest fruit length, weight, width and diameter, while second group had maximum fruit weight, TSS, titratable acidity and highest yield. Principal component analysis (PCA) revealed that first PC, which is the most important component, explained 39.8% of total variation and was positively related to leaf length and leaf length: width ratio, leaf thickness, oil content (fresh and dry-weight basis), stone weight and yield. Among genotypes, most diverse genotypes were Nimla, Summer Glo, Mayfire, Red Globe, Fantasia, Crest Heaven, CITH-P-5, Syria and Punjab Nectarine superior diverse genotypes could be utilized as donor parents to commence crossing in peaches and breeding programmes and may result in genotypes having desired for fruit colour, fruit size, TSS and yield.